Benefits of prophylactic voice prosthesis replacement: a retrospective study - Okła, Sławomir; Spałek, Jakub; Kaliniak, Szczepan; Strzelecka, Agnieszka; Chrobot, Michał; Macek, Paweł; van den Brekel, Michiel W.; Góźdź, Stanisław (Frontiers in Oncology, 2025)
IntroductionIn this retrospective, single-center study conducted at a regional cancer center, we have analyzed whether prophylactic voice prosthesis replacement (PVPR) could reduce the occurrence of tracheoesophageal fistula (TEF) dysfunction.MethodsWe reviewed 2,431 cases of voice prosthesis (VP) replacement procedures performed in 327 patients between January 2017 and December 2022 at the Department of Otolaryngology, Head and Neck Surgery, Holy Cross Cancer Centre, Kielce, Poland. In the middle of this period (January 2020), the management of VP replacements was changed from reactive, unscheduled voice prosthesis replacement (UVPR), with a median device lifetime of 7 months, to prophylactic, scheduled replacement (PVPR) procedures occurring every 3 months.ResultsThe statistical analysis confirmed a significantly lower number of complications during the period of PVPR (2020–2022) compared to the previous period of UVPR (2017–2019). In the years 2017–2019, out of a total of 911 voice prosthesis replacements performed in 246 patients, 425 were associated with complications related to TEF (47%). In comparison, in the years 2020–2022 (following the introduction of PVPR), only 91 cases (6%) (p<0.001; r = 0.408) out of 1,520 voice prosthesis exchanges performed in 250 patients had related TEF complications. The types and occurrence of TEF complications remained the same in both time intervals (UVPR vs. PVPR), with widening of the fistula tract being the most common, comprising 80% and 78% of all TEF complications, respectively.DiscussionPVPR every 3 months can reduce fistula complications compared to a protocol with reactive replacement for voice prosthesis or TEF dysfunction.